PRINCIPLES OF COMPREHENSIVE DEVELOPMENT OF REGIONAL MANAGEMENT BASED ON INNOVATIVE APPROACHES - Mamura Narimanovna Kushakova (European Science Publishing, 2024)
The article analyzes the principles of comprehensive development of the region's management sphere based on innovative approaches. Proposals for promising programs and principles of effectiveness have been developed in the region.
Keywords: Region, innovative approach, integrated development, efficiency, strategy, digital economy.